Investigating the causal relationship between human blood metabolites and pulmonary hypertension: a two-sample Mendelian randomization study - Zeng, Xingdu; Zhong, Bin (Frontiers in Cardiovascular Medicine, 2024)
Background: Several recent investigations have posited that distinct metabolites in the bloodstream may be correlated with the pathogenesis of Pulmonary Hypertension (PH). Nonetheless, the interrelationship between the pathogenesis of PH and metabolite fluctuations remains incompletely elucidated, and findings may differ across studies.In the extant research, data from 486 metabolite-and PH-related genetic variants in human subjects were procured based on Genome-Wide Association Studies (GWAS) and Finnish databases.Univariate Mendelian Randomization analyses were deployed to evaluate the causal relationships between them. The utilization of the randomized Inverse Variance weighted(IVW) method served as the primary analytic framework in this Mendelian Randomization (MR) study. Additionally, four alternative computational strategies, encompassing MR-Egger, were employed as auxiliary methods.A myriad of tests, including Cochran's Q Test, MR-Egger intercept test, MR-PRESSO, leave-one-out analysis, and linkage disequilibrium score were incorporated to assess the robustness of the study outcomes. Metabolite pathway analysis was also executed to identify potential metabolic pathways.Results: After a series of validations and corrected for False discovery rate (FDR), we found a significant association between 1,5-anhydroglucitol (OR=2.00, 95% CI: 1.39-2.89, P=0.0002) and PH, and a significant association between pyridoxalate (OR=0.59, 95% CI: 0.43-0.81, P=0.0009) and 1-a achidonoylglycerophosphocholine (OR=1.78, 95% CI: 1.22-2.58, P=0.0026) had a suggested association with PH. In addition, the vitamin B6 metabolic pathway was also determined to be associated with PH.Conclusively, we isolated 1,5-anhydroglucitol, 1-arachidonoylglycerophosphocholine, and pyridoxate as causally implicated in PH, thereby proffering substantial theoretical substantiation for the formulation of future PH prevention and screening paradigms.